2013
DOI: 10.1002/ejoc.201201300
|View full text |Cite
|
Sign up to set email alerts
|

N‐Heterocyclic Carbene Dirhodium(II) Complexes as Catalysts for Allylic and Benzylic Oxidations

Abstract: The experimental conditions (solvent, base, temperature and oxidant) for allylic and benzylic oxidation reactions catalyzed by dirhodium(II)/N‐heterocyclic carbene (NHC) complexes were optimized for the first time in this work. The oxidations of cyclohexene and fluorene were used as model reactions. Two optimized experimental conditions for both types of oxidations were found, which resulted in their ketone [aerobic conditions, 40 °C, 1 equiv. tBuOOH (TBHP)] or tert‐butyl peroxide derivatives (anaerobic condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Figure shows that the band Rh 2 π* to Rh 2 σ* shifts 107 nm after substrate 1a was added. Previous reports have shown that the energy of Rh 2 π* to Rh 2 σ* HOMO to LUMO transition is strongly affected by axially coordinated ligands. , This large shift indicates that 1a strongly binds to rhodium. Upon adding one portion of T-HYDRO, the UV/vis spectrum remained relatively unchanged and there was no band that corresponded to typical one-electron oxidized Rh 2 (II,III) species (about 800 nm).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Figure shows that the band Rh 2 π* to Rh 2 σ* shifts 107 nm after substrate 1a was added. Previous reports have shown that the energy of Rh 2 π* to Rh 2 σ* HOMO to LUMO transition is strongly affected by axially coordinated ligands. , This large shift indicates that 1a strongly binds to rhodium. Upon adding one portion of T-HYDRO, the UV/vis spectrum remained relatively unchanged and there was no band that corresponded to typical one-electron oxidized Rh 2 (II,III) species (about 800 nm).…”
Section: Resultsmentioning
confidence: 85%
“…Interestingly, while Rh 2 (OAc) 4 has a nearly identical potential for one-electron oxidation compared to Rh 2 (esp) 2 , using Rh 2 (OAc) 4 only gave a 35% yield. Rh 2 (OAc) 4 (IMes) was also tested but only gave 71% yield . Low yields were obtained when carrying out the reaction with structurally similar chelating dirhodium­(II) catalysts …”
Section: Resultsmentioning
confidence: 99%
“…As mentioned in the Introduction, the cause of low yields in redox-active metal (Rh, Fe)-complexes catalyzing oxidations of organic substrates by alkyl hydroperoxides have sporadically been ascribedwithout experimental verificationto a putative background dismutation. Aside from the oxidation of organic substrates, alkyl hydroperoxides are routinely used in the preparation of high-valent metal complexes. In these syntheses it would seem that ample opportunities for the observation of disproportionation have been available to the many workers in the area of high-valent biomimetic first-row transition metal complexes: The dearth of observations of this specific reaction is surprising.…”
Section: Resultsmentioning
confidence: 99%
“…Solutions containing cumene hydroperoxide are sold under the trademark Trigonox K-90 or Trigonox 239a. Alkyl peroxides are also used extensively as terminal oxidants in industrial- and laboratory-scale organic syntheses. Disproportionation of the alkyl peroxides has been sporadically suggested as a possible reason for reduced yields in catalytic selective substrate oxidations; however, the impact of unproductive reactions has never been evaluated in detail nor the release of product O 2 directly measured.…”
Section: Introductionmentioning
confidence: 99%
“…Different dirhodium­(II) catalysts were also screened, with only Rh 2 (OAc) 4 , Rh 2 (TFA) 4 , and Rh 2 (Oct) 4 producing the desired product 2a at yields ranging from 25 to 39% (Table , entries 14–16). Additionally, Rh 2 (OAc) 4 (IMes) and the structurally similar chelating dirhodium­(II) catalyst Rh 2 (MPDP) 2 were found to be less efficient compared with Rh 2 (esp) 2 (Table , entries 17–18). Further evaluation revealed that reducing the catalyst loading to 0.1 mol % Rh 2 (esp) 2 catalyzed the reaction but only resulted in a 50% yield after 6 h (Table , entry 19).…”
Section: Resultsmentioning
confidence: 99%